The chemistry maths book - Steiner, Erich, 1937- (Oxford University Press, 2008)
"Topics are organized into three parts: algebra, calculus, differential equations, and expansions in series; vectors, determinants and matrices; and numerical analysis and statistics. The extensive use of examples illustrates every important concept and method in the text, and are used to demonstrate applications of the mathematics in chemistry and several basic concepts in physics. The exercises at the end of each chapter, are an essential element of the development of the subject, and have been designed to give students a working understanding of the material in the text."--Jacket.
Keywords: Mathematics.; Chemistry -- Mathematics.; elektronické knihy; electronic books